Tests of lepton universality using B0→K0Sℓ+ℓ− and B+→K*+ℓ+ℓ− decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2022)
Tests of lepton universality in B0→K0Sℓ+ℓ− and B+→K*+ℓ+ℓ− decays where ℓ is either an electron or a muon are presented. The differential branching fractions of B0→K0Se+e− and B+→K*+e+e− decays are measured in intervals of the dilepton invariant mass squared. The measurements are performed using proton-proton collision data recorded by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1 . The results are consistent with the standard model and previous tests of lepton universality in related decay modes. The first observation of B0→K0Se+e− and B+→K*+e+e− decays is reported.